DIGITAL TRANSFORMATION AND FINANCIAL INCLUSION: THE IMPACT OF FINTECH DEVELOPMENT ON ECONOMIC GROWTH IN DEVELOPING COUNTRIES (Eureka Journal of Computing Science & Digital Innovation, 2026)
This study examines the impact of fintech development on financial inclusion and economic growth in developing countries. Using panel data from 25 developing economies over the period 2010–2024, the research investigates whether the expansion of digital financial services contributes to GDP growth through improved financial inclusion. The study applies fixed-effects and random-effects panel regression models, supported by Hausman specification tests. Key variables include mobile money penetration, digital payment adoption, internet usage rates, and financial access indicators. The results demonstrate that fintech expansion significantly improves financial inclusion and positively affects economic growth.
Keywords: Fintech, Financial Inclusion, Digital Economy, Economic Growth, Panel Data, Developing Countries.